2010
DOI: 10.1037/a0021034
|View full text |Cite
|
Sign up to set email alerts
|

Postidentification feedback affects subsequent eyewitness identification performance.

Abstract: Eyewitnesses sometimes view more than one lineup during an investigation. We investigated the effects of postidentification feedback following one lineup on responses to a second lineup. Witnesses (N=621) viewed a mock crime and, later, attempted to identify the culprit from an initial (target-absent) lineup and a second (target-present or target-absent) lineup. Prior to viewing the second lineup, some witnesses received accurate feedback stating that the initial lineup did not contain the culprit. A compound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 58 publications
(79 reference statements)
4
97
0
Order By: Relevance
“…One possibility is that the presence of the option to withhold their answer encourages participants to change what memorial evidence they evaluate in order to make a lineup decision, compared with participants required to report an answer. Similar claims have been made for lineup decisions following observations of changes in memory accuracy following feedback about a different lineup (Palmer, Brewer, & Weber, 2010), verbal description of irrelevant material (Westerman & Larsen, 1997), and induction of processing style (Perfect, Dennis, & Snell, 2007;Wyer, Perfect, & Pahl, 2010). Such observations highlight the importance of understanding the processes that underlie performance on memory tasks involving complex, compound decisions.…”
Section: The Koriat and Goldsmith (1996) Controi Frameworkmentioning
confidence: 64%
“…One possibility is that the presence of the option to withhold their answer encourages participants to change what memorial evidence they evaluate in order to make a lineup decision, compared with participants required to report an answer. Similar claims have been made for lineup decisions following observations of changes in memory accuracy following feedback about a different lineup (Palmer, Brewer, & Weber, 2010), verbal description of irrelevant material (Westerman & Larsen, 1997), and induction of processing style (Perfect, Dennis, & Snell, 2007;Wyer, Perfect, & Pahl, 2010). Such observations highlight the importance of understanding the processes that underlie performance on memory tasks involving complex, compound decisions.…”
Section: The Koriat and Goldsmith (1996) Controi Frameworkmentioning
confidence: 64%
“…The witness who does not make an initial lineup identification may commit to a strategy of not choosing, perhaps informed or compelled by his or her seeming lack of success at the earlier identification (Palmer, Brewer, & Weber, 2010). A well-constructed lineup offers the protection of fillers, lineup members intentionally selected to possess physical attributes similar to the offender (unlike a mugshot search).…”
Section: Non-suspect/suspect Decisionsmentioning
confidence: 99%
“…Previous dual-lineup studies (Hinz & Pezdek, 2001;Palmer et al, 2010;Pezdek & Blandon-Gitlin, 2005) employed culprit-absent lineups as the first ('intervening') lineup, finding a negative impact on witness accuracy at a second lineup. Previous dual-lineup studies (Hinz & Pezdek, 2001;Palmer et al, 2010;Pezdek & Blandon-Gitlin, 2005) employed culprit-absent lineups as the first ('intervening') lineup, finding a negative impact on witness accuracy at a second lineup.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%
“…Such findings are useful generally for showing that person recognition is susceptible to feedback, but do not actually demonstrate improvements in identification performance. However, more recently such an improvement with feedback has also been found in an eyewitness identification paradigm (Palmer, Brewer, & Weber, 2010). In this study, observers were shown a video of a staged crime, which was followed by two photographic identity lineups.…”
mentioning
confidence: 99%